One-piece cast iron brake drum with morphological layering and preparation method thereof
Through the integrated molding process, cast iron brake drum with morphological layering is prepared, which solves the crack defect problem caused by the difference in material thermal conductivity coefficient of the existing brake drum at high temperature, significantly improves the reliability and bonding strength of the brake drum, and simplifies the process flow.
Patent Information
- Application Number
- CN202211007715.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-08-22
AI Technical Summary
At high temperatures, the temperature difference between the inner and outer layers of the existing brake drums is large due to the difference in the thermal conductivity of the material, which is prone to crack defects, which reduces reliability. The composite bimetal brake drums have complex processes and high costs.
The integrated molding process is adopted to prepare a cast iron brake drum with morphological layering. The outer layer is a high-strength ductile iron layer, a spherical + worm-shaped graphite transition layer in the middle, and an wear-resistant gray cast iron layer. The overall matrix structure is the same to eliminate crack defects caused by differences in thermal conductivity.
It significantly improves the reliability of the brake drum, combines the increase in strength, has low process energy consumption, high yield, and is relatively simple in process.
Smart Images

Figure CN115351229B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake drums, and in particular to an integrally formed cast iron brake drum with morphological layers and a preparation method thereof. Background Art
[0002] The working environment and working conditions of heavy-duty vehicle brake drums are relatively harsh. The huge braking torque generated during emergency braking of the vehicle will generate a large amount of friction heat on the inner working surface of the brake drum in contact with the friction material. Due to the large wall thickness of the brake drum and the limitation of the thermal conductivity of the material, the heat generated by braking cannot be completely and timely dissipated through convection, conduction, etc., resulting in a large temperature difference between the inner and outer surfaces of the brake drum, which in turn causes the brake drum to fail. Most of the failures of the three guarantees of the brake drum are cracking, followed by cracking and bottoming; and the failure of the brake drum can easily cause safety accidents.
[0003] The brake drums currently used in the market include traditional gray cast iron brake drums, composite bimetallic brake drums with outer steel plates and inner gray cast iron, bimetallic brake drums formed by two pourings of ductile iron and gray iron, and brake drums with an outer cast steel layer and an inner gray iron layer formed by one pouring. Traditional gray cast iron brake drums are prone to failure and have low market acceptance. Compared with traditional gray iron brake drums, the double-molded bimetallic brake drums have a steel plate or high-strength ductile iron outer layer and a gray iron inner layer, which to a certain extent improves the strength of the brake drum and reduces failure. However, the outer shell and the inner lining are molded twice, and defects are easily generated at the intermediate joint, which are difficult to effectively detect, posing quality and safety risks. At the same time, whether it is the process of outer spinning steel plate or casting ductile iron and centrifugally casting the inner gray iron, there are problems such as complex procedures, long production cycles, and high production costs.
[0004] Patent CN110657175A discloses a composite brake drum and a preparation method thereof, which uses cast steel as a matrix, and the inner layer is made close to gray cast iron by controlling the material of the composite layer. In the specific preparation process, a carburizing agent composed of multiple substances is used. Although it is cast in one time, the linear shrinkage rate of cast steel is 1.5-2%, and the linear shrinkage rate of cast iron is 0.7%-1%. Due to the difference in the materials themselves, the process yield rate of steel castings is significantly lower than that of iron castings.
[0005] At the same time, the pouring temperature of cast steel is more than 200℃ higher than that of cast iron, which consumes a lot of energy. Moreover, the patent controls the material of the composite layer to form an inner layer similar to gray cast iron, which has a thinner wall thickness and a shorter solidification time. The carbon in the composite layer is not easy to dissolve, and it is difficult to increase carbon, so the quality cannot be effectively controlled. Summary of the invention
[0006] In view of this, the object of the present invention is to provide an integrally molded cast iron brake drum with morphological layering and a preparation method thereof, so that the cast iron brake drum is integrally molded with a high-strength ductile iron layer on the outer layer, a spherical + worm-shaped graphite transition layer in the middle, and a wear-resistant gray cast iron layer on the inner layer. The overall matrix structure is the same, eliminating the crack defects of the inner and outer layers caused by the difference in thermal conductivity between different materials at high temperature, thereby significantly improving the reliability of the brake drum.
[0007] In order to solve the above technical problems or at least partially solve the above technical problems, the present invention provides a method for preparing an integrally formed cast iron brake drum with morphological layers, comprising:
[0008] Step 1, using hot core resin sand or cold core resin sand to prepare a sand core, wherein a mixture of elemental sulfur and / or iron sulfide and iron oxide is added to the sand core during the sand mixing process;
[0009] Step 2: Apply a coating containing elemental sulfur and / or iron sulfide to the outer surface of the prepared sand core and dry it;
[0010] Step 3: Place the dried sand core into the outer sand mold and assemble the mold for pouring;
[0011] Step 4, spheroidizing the original iron water and then pouring;
[0012] In certain embodiments of the present invention, the composition of the molten iron after spheroidization is as follows:
[0013] C: 3.8%, Si: 2.3%, Mg: 0.04%, Re: 0.035%, S: 0.01%; or
[0014] C: 3.9%, Si: 2.1%, Mn: 0.6%, Cu: 0.8%, Mg: 0.045%, Re: 0.035%, S: 0.01%.
[0015] Step 5: After pouring, cool and remove sand, and clean the brake drum casting.
[0016] In certain embodiments of the present invention, the amount of elemental sulfur and / or iron sulfide added in step 1 is 1.5-10% of the mass of the sand core; in a specific embodiment of the present invention, 5% elemental sulfur is added during the sand mixing process in step 1.
[0017] In certain embodiments of the present invention, the amount of iron oxide added in step 1 is 0.5-2% of the mass of the sand core; in a specific embodiment of the present invention, 0.5% of red iron oxide powder is added during the sand mixing process of step 1.
[0018] In certain embodiments of the present invention, the outer mold sand mold is cast using green sand or resin sand.
[0019] In certain embodiments of the present invention, the coating in step 2 is a commercially available conventional coating for casting sand cores. The amount of sulfur and / or iron sulfide added is 15-30% of the coating mass; in a specific embodiment of the present invention, 15% elemental sulfur is added to the coating.
[0020] In certain embodiments of the present invention, the spheroidization process adopts a punching spheroidization process, a covering spheroidization process or a wire feeding spheroidization process.
[0021] In certain embodiments of the present invention, the composition of the original molten iron (before spheroidization) is eutectic or hypereutectic, and the composition includes C: 3.6-4.0%, Si: 1.4-1.8%, S: ≤0.03%. In a specific embodiment of the present invention, the original molten iron (before spheroidization) is controlled according to the composition required by QT450, QT500, QT600, QT700 or higher strength.
[0022] In certain embodiments of the present invention, the casting temperature of the cast iron brake drum is controlled at 1360-1420°C; in a specific embodiment of the present invention, the casting temperature is 1395°C.
[0023] The cast iron brake drum prepared according to the preparation method of the present invention has the same overall matrix structure and has a distribution of ductile iron layer, spherical + worm-shaped graphite transition layer and gray cast iron layer from outside to inside, which significantly improves the reliability of the brake drum. At the same time, through the analysis of the addition of elemental sulfur or iron sulfide and iron oxide, iron oxide not only has the function of indicating whether the sand mixing is uniform, but also affects the thickness of the graphite transition layer and the gray cast iron layer. Failure to add iron oxide will lead to a thicker graphite transition layer, and the corresponding ductile iron layer will become thinner, reducing the tensile strength of the brake drum; and the lack of elemental sulfur or iron sulfide will cause the gray cast iron layer to be less than 3mm. The thickness distribution of each layer of the cast iron brake drum prepared by the present invention is reasonable, which can significantly improve the tensile strength and has better yield strength and elongation.
[0024] Based on the technical effects of the above cast iron brake drum, the present invention also provides a cast iron brake drum prepared by the preparation method of the present invention, whose outer layer is a ductile iron layer, the middle is a spherical + worm-shaped graphite transition layer, and the inner layer is a gray cast iron layer.
[0025] In certain embodiments of the present invention, the thickness of the graphite transition layer of the cast iron brake drum is not more than 4 mm, in other embodiments of the present invention, the thickness of the graphite transition layer is 1-4 mm, in other embodiments of the present invention, the thickness of the graphite transition layer is 2.3 mm; in certain embodiments of the present invention, the thickness of the gray cast iron layer is 3-8 mm, in other embodiments of the present invention, the thickness of the gray cast iron layer is 6.5 mm.
[0026] It can be seen from the above technical scheme that the cast iron brake drum described in the present invention adopts a one-time production molding process technology to prepare a cast iron brake drum with the same overall matrix structure and different graphite morphology layered distribution. Compared with traditional steel and iron-iron composite brake drums, the defects existing in the two molding processes are eliminated, the bonding strength is significantly improved, and the graphite transition layer realizes a smooth transition between the outer wall metal and the inner wall metal. The entire preparation process has low energy consumption, high yield and relatively simple process. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The figure shows a schematic diagram of the cross-sectional structure of the cast iron brake drum of the present invention; 1 represents the outer ductile iron layer, 2 represents the middle graphite transition layer, and 3 represents the inner gray cast iron layer;
[0028] Figure 2 4 represents the upper mold of the outer mold sand mold, 5 represents the lower mold of the outer mold sand mold, 6 represents the molten iron pouring port, 7 represents the sand core, and 8 represents the coating area on the surface of the sand core (corresponding to the inner wall area of the brake drum);
[0029] Figure 3 Shown is a metallographic microscope image of the matrix structure of the cast iron brake drum of the present invention. DETAILED DESCRIPTION
[0030] The present invention discloses an integrally formed cast iron brake drum with morphological layering and a method for preparing the same. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The brake drum production process of the present invention has been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the brake drum and the method for preparing the same described in this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.
[0031] The present invention specifically provides a method for preparing an integrally formed cast iron brake drum with morphological layers, comprising:
[0032] (1) The inner wall of the brake drum is formed by hot core resin sand or cold core resin sand, that is, the preparation of the sand core; the outer wall is formed by resin sand or green sand process, that is, the preparation of the outer mold sand mold; wherein, the shapes of the sand core and the outer mold sand mold are not specifically limited and can be prepared as required;
[0033] When preparing sand cores, 1.5%-10% sulfur or iron sulfide powder or a mixture thereof (to increase sulfur and form an inner wall gray cast iron layer) and 0.5%-2% red iron oxide powder (to indicate whether the mixing is uniform and to control the thickness of the graphite transition layer) need to be added during the sand mixing process;
[0034] The outer surface of the sand core (corresponding to the inner wall area of the brake drum) needs to be painted, and 15%-30% of sulfur or iron sulfide or a mixture thereof needs to be added to the paint (sulfurization forms an inner wall gray cast iron layer).
[0035] The sand core after coating is dried and placed into the prepared outer mold sand mold, and the box is assembled for pouring (see the schematic diagram of the structure after the box is assembled) Figure 2 );
[0036] (2) The composition of brake drum molten iron (before spheroidizing treatment) is controlled according to the composition required by QT450, QT500, QT600, QT700 or higher strength, with the composition of C: 3.6-4.0%, Si: 1.4-1.8%, S ≤ 0.03%;
[0037] (3) The pouring method, the covering method or the wire feeding spheroidization process can be selected for spheroidization treatment and pouring, and the pouring temperature of the brake drum is controlled at 1360-1420℃;
[0038] (4) After pouring, the production line is cooled and sand removed, and the brake drum casting is cleaned. The cross-sectional structure diagram of the cast iron brake drum is shown in Figure 1 .
[0039] The following is a further description of an integrally formed cast iron brake drum with morphological layers and a preparation method thereof provided by the present invention.
[0040] Example 1: Preparation of cast iron brake drum of the present invention
[0041] The cast iron brake drum is cast using QT450-10 molten iron. The one-shot cast iron brake drum of this embodiment is formed by horizontal green sand casting.
[0042] The inner wall of the brake drum is formed by cold core resin sand core. 5% elemental sulfur and 0.5% red iron oxide powder are added during the sand mixing process. After mixing, it is put into the sand hopper and shot into the mold by the core shooting machine for forming.
[0043] Add 15% elemental sulfur to the commercially available sand core coating, stir thoroughly, and evenly apply it on the outer surface of the sand core (corresponding to the inner wall area of the brake drum);
[0044] Use horizontal green sand molding line to mold, put the dried sand core into the finished outer sand mold, and then close the box for pouring;
[0045] Prepare molten iron according to QT450-10 process, use flushing method to spheroidize, and pour the molten iron into the mold with a pouring temperature of 1395℃.
[0046] The chemical composition of molten iron after spheroidization is as follows:
[0047] C: 3.8%
[0048] Si: 2.3%
[0049] Mg: 0.04%
[0050] Re: 0.035%
[0051] S: 0.01%
[0052] After pouring, the production line is cooled, sand is removed, and the brake drum casting is cleaned. The finished product rate of the prepared cast iron brake drum is greater than 95%, the tensile strength is greater than or equal to 450MPa, the yield strength is greater than or equal to 310MPa, and the elongation is greater than or equal to 10%.
[0053] Example 2: Preparation of cast iron brake drum of the present invention
[0054] The cast iron brake drum is cast using as-cast QT700-5 molten iron. The one-shot cast iron brake drum of this embodiment is formed by green sand casting. The manufacturing method is based on Example 1.
[0055] Among them, the chemical composition of molten iron after spheroidization is as follows:
[0056] C: 3.9%
[0057] Si: 2.1%
[0058] Mn: 0.6%
[0059] Cu: 0.8%
[0060] Mg: 0.045
[0061] Re: 0.035%
[0062] S: 0.01%.
[0063] After pouring, the production line is cooled, the sand is removed, and the brake drum casting is cleaned. The finished product rate of the prepared cast iron brake drum is greater than 95%, the tensile strength is greater than 700MPa, the yield strength is greater than 410MPa, and the elongation is greater than 5%.
[0064] Comparative Example: Preparation of a control cast iron brake drum
[0065] In this embodiment, each group uses as-cast QT700-2 molten iron for pouring;
[0066] The present invention: Prepared by referring to the preparation method of Example 1;
[0067] Comparative Example 1: Referring to the preparation method of Example 1, the difference is that no elemental sulfur is added during the sand core preparation process;
[0068] Comparative Example 2: The preparation method is similar to that of Example 1, except that no sulfur is added to the coating.
[0069] Comparative Example 3: Referring to the preparation method of Example 1, the difference is that no iron oxide is added during the sand core mixing process;
[0070] The brake drums prepared in the above three comparative examples were subjected to relevant performance tests, and the results are shown in Table 1 below;
[0071] Table 1
[0072] Graphite transition layer thickness (mm) Gray cast iron layer thickness (mm) The present invention 2.3 6.5 Comparative Example 1 3.1 2.2 Comparative Example 2 2.9 2 Comparative Example 3 5.7 7
[0073] As can be seen from Table 1, the thickness of the graphite transition layer and the gray cast iron layer of the present invention is moderate, which not only ensures the wear resistance of the brake drum, but also improves the strength. The reliability of the brake drum is significantly improved, while the other comparative examples cannot make the thickness of the graphite transition layer and the gray cast iron layer at the ideal thickness, and thus cannot ensure the reliability of the brake drum.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an integrally formed cast iron brake drum having morphological layers, characterized in that: include: Step 1, using hot core resin sand or cold core resin sand to prepare a sand core, and adding a mixture of elemental sulfur and / or iron sulfide powder with a particle size less than 100 mesh and iron oxide during the sand mixing process of the sand core; the amount of elemental sulfur and / or iron sulfide added is 1.5-10% of the mass of the sand core, and the amount of iron oxide added is 0.5-2% of the mass of the sand core; Step 2: Apply a coating containing elemental sulfur and / or iron sulfide to the outer surface of the prepared sand core and dry it in the air; the amount of sulfur and / or iron sulfide added is 15-30% of the coating mass. Step 3: Place the dried sand core into the outer sand mold and assemble the mold for pouring; Step 4: spheroidize the original molten iron and then pour it; the composition of the molten iron after spheroidization is as follows: C: 3.8%, Si: 2.3%, Mg: 0.04%, Re: 0.035%, S: 0.01%; or C: 3.9%, Si: 2.1%, Mn: 0.6%, Cu: 0.8%, Mg: 0.045%, Re: 0.035%, S: 0.01%; Step 5: After pouring, cool and remove sand, and clean the brake drum casting.
2. The preparation method according to claim 1, characterized in that: The outer mold sand mold is cast by green sand or resin sand.
3. The preparation method according to claim 1, characterized in that: The spheroidization treatment adopts a punching spheroidization process, a covering spheroidization process or a wire feeding spheroidization process.
4. The preparation method according to claim 1, characterized in that: The original molten iron has a composition of eutectic or hypereutectic, and the composition includes C: 3.6-4.0%, Si: 1.4-1.8%, and S: ≤0.03%.
5. The cast iron brake drum prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The outer layer is a ductile iron layer, the middle layer is a spherical + worm-shaped graphite transition layer, and the inner layer is a gray cast iron layer.
6. The cast iron brake drum according to claim 5, characterized in that: The thickness of the graphite transition layer is no more than 4 mm, the thickness of the gray cast iron layer is 3-8 mm, and the remaining part is the thickness of the ductile iron layer.
Citation Information
Patent Citations
Novel brake drum
CN114033818A
Cast iron piston and its production
JP1983209443A
Casting method and mold coating material used therein
JP1985238058A
Method for producing spheroical graphite cast iron product
JP2001269767A